Stakeholders' Awareness, Understanding, and Acceptability of the Goals and Objectives of a Sports Science and Exercise Program: Basis for Formative Curriculum Evaluation - Marites S. Florentino (Kharkiv State Academy of Physical Culture, 2023)
Purpose: This study aimed to assess the awareness, understanding, and acceptability of the goals and objectives of a sports science program in the Cagayan State University, Philippines among stakeholders, including students, faculty, and industry professionals. Material and Methods: A survey was conducted using a self-administered questionnaire to collect data from 342 stakeholders. The questionnaire consisted of items related to stakeholders' demographic profile, awareness and understanding of the program's goals and objectives, and their acceptability of the program. Results: Results showed that stakeholders had a moderate level of awareness, acceptability, and understanding of the program's goals and objectives, with internal stakeholders having higher understanding in general than external stakeholders. Conclusion: The study concludes that there is a need to improve communication and collaboration between the program and external stakeholders to increase their understanding and acceptance of the program's goals and objectives. The findings of this study can serve as a basis for formative curriculum evaluation and curriculum improvement, enabling the program to better meet the needs of students and the industry.